Remediation of Wastewater from Chlorpyrifos Pesticide by Nano-Gold Photocatalyst. (2020) - Goel, Puja; Arora, Manju
Abstract: Successful disintegration of Chlorpyrifos pesticide by nearly monodisperse nano-gold photcatalyst (∼10 nm) for remediation of wastewater has been reported in current studies. Nano-Gold dispersion reaction with Chlorpyrifos solutions completes in 45 minutes at ambient temperature under the normal daylight and exhibit systematic variations in the solution color from wine red to pink to light sky blue and finally transforming into a transparent solution with fine precipitates. UV-Vis absorption studies correlates well with the systematic color changes as observed in the nano-gold treated Chlorpyrifos solutions with time. The characteristic localized surface plasmon resonance peak of nanogold dispersion observed at 529 nm red shifts to weak, medium and strong intensity peaks at ∼ 640 nm, 740 nm and 890 nm on increasing chlorpyrifos concentration owing to the aggregation of gold nanoparticles in small to bigger sized clusters. The fine turbidity in final transparent solution further confirms the aggregation of nanogold particles into stable bigger ensembles. IR transmission spectra of final transparent solutions showed disappearance of Chlorpyrifos νC-Cl and phosphorothioate functional group peaks indicating degradation of chlorpyrifos.